The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s13014-021-01908-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome and compliance to dose-intensified linac-based SBRT for unfavorable prostate tumors using a novel real-time organ-motion tracking

Abstract: Purpose/objectives To report preliminary data on treatment outcome and compliance to dose-intensified organ sparing SBRT for prostate cancer using a novel electromagnetic transmitter-based tracking system (RayPilotÒ System) to account for intra-fractional organ motion. Material/methods Thirteen patients with intermediate unfavorable (9) and selected high-risk (4) prostate cancer underwent dose-escalated SBRT in 4 or 5 fractions (BED1.5 = 279 Gy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…In the context of extreme hypofractionation, even a single fraction with unexpected organ motion can lead to potentially detrimental dosimetric and clinical consequences. The excellent early toxicity rates, compliance, and biochemical outcomes seen in the present series ( 23 ) suggest that treatment was delivered accurately and precisely.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the context of extreme hypofractionation, even a single fraction with unexpected organ motion can lead to potentially detrimental dosimetric and clinical consequences. The excellent early toxicity rates, compliance, and biochemical outcomes seen in the present series ( 23 ) suggest that treatment was delivered accurately and precisely.…”
Section: Discussionsupporting
confidence: 51%
“…Patient population and treatment planning protocol have been described previously ( 23 ). Briefly, patients were immobilized in the supine position with arms over their chest using the FeetFix system (CIVCO Medical Solutions, Iowa, US) attached to the couch for ankle fixation.…”
Section: Methodsmentioning
confidence: 99%
“…However, a few single-arm prospective studies have reported lower acute GU and GI toxicity using small clinical target volume to PTV margin using conventional methods. [5][6][7] Another approach to reducing GU toxicity can be to improve urethra delineation, which can be a reason for reduced GU toxicity in the MIRAGE MRI group. 1 A phase-2 study involving 170 patients treated on CT-based LINACs reported acute grade 2 GU toxicity of 18% with urethra-sparing SBRT using a 5-mm margin all around except posteriorly (3 mm).…”
Section: Related Articlementioning
confidence: 99%
“…As highlighted by the Kishan et al study, no randomized data support using 2-mm PTV margins for prostate SBRT. However, a few single-arm prospective studies have reported lower acute GU and GI toxicity using small clinical target volume to PTV margin using conventional methods . Another approach to reducing GU toxicity can be to improve urethra delineation, which can be a reason for reduced GU toxicity in the MIRAGE MRI group .…”
mentioning
confidence: 99%
“…Furthermore, late grade ≥3 genitourinary and gastrointestinal toxicity were found in 2.3% and 0.9% patients, respectively. Lucchini et al 61 assessed dose-intensified linac-based SBRT using novel real-time organ motion tracking in unfavorable prostate cancer (n = 13). The patients were delivered SBRT in 4 or 5 fractions, and preliminary findings revealed that RTOG grade ≥3 genitourinary toxicity was observed in 2% and 2% patients in the 2 groups, respectively, with no treatment-related deaths.…”
Section: Genitourinary and Gastrointestinal Toxicitymentioning
confidence: 99%